The impact of customer involvement in airline loyalty programs: a multigroup analysis - Pablo Flôres Limberger; Lucimari Acosta Pereira; Tércio Pereira (Tourism & Management Studies)
Loyalty programs (LPs) have been considered a key determining factor for the performance of many companies. Although the benefits, satisfaction, perceived functional value (PFV), and loyalty (BSPfvL) have been widely explored, few studies have attempted to compare the results of this model in different groups of consumers. This study aims to analyze the relationships for varying levels of user involvement in airline loyalty programs. The population of this study was individual members of airway loyalty programs in Brazil. We obtained 429 answered questionnaires. We used multi-group analysis (MGA) using Partial least squares structural equation modeling (PLS-SEM). The results of this study indicate the mediation effect of satisfaction and perceived value and moderation of consumer involvement. A difference was identified between the two groups regarding hedonic benefits, satisfaction, and loyalty. This research has successfully contributed to the airline industry regarding the importance of loyalty benefits. Additionally, it highlights the importance of establishing consumers’ involvement in company loyalty programs. Finally, this study provides practical and theoretical contributions and guides future research efforts.